2000
DOI: 10.1099/0022-1317-81-3-577
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the 3′-terminal untranslated region of tobacco mild green mosaic tobamoviruses from Nicotiana glauca resulting in variants with three or six pseudoknots

Abstract: Isolates of tobacco mild green mosaic tobamovirus (TMGMV) were obtained from 58 plants of Nicotiana glauca in southern California and placed in one of two groups (Small type and Large type) based on the size of the subgenomic RNA for the coat protein (CP). The CP sequence differed by no more than one amino acid for the two types, and the Small type was identical to that published for TMGMV. Thirty-six of the isolates had a double-stranded (ds)RNA profile that matched that of type TMGMV, and the nucleotide sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…A second posibility is that TMGMV infects other, nonidentified hosts in the same region, in which an alanine at CP position 148 would be advantageous. The 3= UTR-length dimorphism has been reported in the TMGMV population infecting N. glauca in California (60,61), and it was shown that isolates with a long 3= UTR outcompeted those with a short one (61). In our isolate collection, however, the 3= UTR length was not associated with differential levels of virus multiplication in N. glauca, but in pepper, isolates having a short 3= UTR had an advantage.…”
Section: Discussionsupporting
confidence: 50%
“…A second posibility is that TMGMV infects other, nonidentified hosts in the same region, in which an alanine at CP position 148 would be advantageous. The 3= UTR-length dimorphism has been reported in the TMGMV population infecting N. glauca in California (60,61), and it was shown that isolates with a long 3= UTR outcompeted those with a short one (61). In our isolate collection, however, the 3= UTR length was not associated with differential levels of virus multiplication in N. glauca, but in pepper, isolates having a short 3= UTR had an advantage.…”
Section: Discussionsupporting
confidence: 50%
“…Of the three strains, U2 and U5 have been described from the United States, 8,9 and they differ in the size in their 3 0 untranslated regions (UTR). Strain TMGMV-U5 has a repeated sequence of 147-nucleotides in the 3´UTR compared with TMGMV-U2.…”
Section: Introductionmentioning
confidence: 99%
“…It illustrates the high flexibility in the make-up of 39 ends among these virus genera, which is presumably due to recombination events in doubly infected plant hosts. This suggestion is supported by the occurrence of frequent duplications of UPDs and parts of the TLS in several tobamoviruses (Gultyaev et al, 1994;Bodaghi et al, 2000;Ruiz del Pino et al, 2003). In view of the observations summarized in Figs 5 and 7, it might not be surprising if some day a pomo-or furovirus would be detected with an RNA that has a histidylatable TLS on its 39 end rather than the common valylatable TLS.…”
Section: Discussionmentioning
confidence: 80%